2017
DOI: 10.23956/ijermt/v6n1/117
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Various Process Parameters Using Response Surface Methodology for Exopolysaccharide Production from a Novel Strain Pediococcus acidilactici KM0 (Accession Number KX671557) Isolated from Milk Cream

Abstract: Abstractediococcus acidilactici KM0 (accession number KX671557) isolated from milk cream was optimized by response surface methodology by using the Design Of Experiments (DOE) to evaluate the interactive effects of the process parameters i.e. incubation time (h), temperature (•C), pH, carbon concentration, nitrogen concentration production for the production of EPS . Maximum EPS production of 32.64 mg/ml observed after 24 h incubation at 35 •C using 1.50 % and 3% of carbon and nitrogen concentration respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Sharma et al . (2017) reported that the temperature, incubation time, pH, nitrogen and carbon concentrations are the main factors that positively affect EPS bioproduction. They found that the maximum EPS amount produced by P .…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al . (2017) reported that the temperature, incubation time, pH, nitrogen and carbon concentrations are the main factors that positively affect EPS bioproduction. They found that the maximum EPS amount produced by P .…”
Section: Resultsmentioning
confidence: 99%
“…Haroun et al, (2013) confirmed that Lactobacillus plantarum produced the highest amount of EPS when the pH was 6.2. Sharma et al, (2017) discovered that Pediococcus acidilactici produced maximum EPS at pH 6.0 after a 24-hour incubation period at 35 °C. Results of the inoculation amount effect have been shown by many researchers (Sivakumar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%